KEEFEKTIFAN PENGGUNAAN COGNITIVE-BEHAVIORAL THERAPY (CBT) SEBAGAI TERAPI PADA KONSELING MASALAH PSIKOLOGIS (SEBUAH STUDI DESKRIPTIF) - Gunawan Simondinata; Juliana Hindradjat (Universitas Kristen Immanuel, 2024)
Guidance and counseling is a widely used practice in various fields. In thisarticle, the effectiveness of Guidance and Counseling using CBT will be discussed. This isa qualitative research with descriptive method.[a1] The effectiveness of CBT has beenproven and reported in the NIH (National Library of Medicine). In Japan, CBT for mooddisorders was first covered under the National Health Insurance (NHI), and CBT for thefollowing psychiatric disorders was later added to the NHI scheme: obsessive-compulsivedisorder, social anxiety disorder, panic disorder, post-traumatic stress disorder, andbulimia nervosa. In Indonesia, research results show that CBT counseling techniques areeffective for increasing the self-efficacy of students of SMAN 2 Bandung in mathematics.